Improved phaco needle for dense nucleus (Ukrainian Journal of Ophthalmology, 2026)
Background: Phacoemulsification (phaco) of the dense nuclear cataract tends to be associated with difficulties caused by impossibility of breaking the nucleus up completely. Therefore, the development of a phaco needle allowing for an improved capacity of ultrasound to destroy the dense nucleus with minimal ultrasound expense is important.Purpose: To improve a phaco needle for dense nucleus in order to allow for a more effective destruction (fragmentation and cutting) of the lens and aspiration of fine lens matter through a reduction in a level of lens exposure to ultrasound from the needle.Materials and Methods: Forty-six patients (50 eyes) underwent phacoemulsification with intraocular lens implantation. In 23 cases, the surgeon used the conventional phaco chop nucleus-dividing technique with the aid of an advanced phaco needle. No intraoperative complication was observed.Results: We have developed an improved phaco needle which has the following feature when compared with a conventional one: the end surface of the flared portion has a plurality of isosceles teeth, allowing the needle to penetrate the nucleus and remove the phaco debris more efficiently. The use of the needle allowed for a reduction in the level of eyeball exposure to ultrasound, thus reducing the risk of intra- and postoperative complications in patients with dense nuclear cataracts.
Keywords: phaco needle; dense nuclei; cataract